giải
giải
giải
α a+ bi a −b +2 abi
α =a+bi→ = = 2 2
α a−bi a +b
ά =α
ℜ ( z )=a
c= √ ( x−a ) + ( y−b )
2 2
z=x + yi
w=a +bi
Pn ( z )=Pn ( z )
z +w=z +w
n n n
Pn ( z )=∑ a k z k =∑ a k z k =∑ ak z k =Pn ( z )
k=0 k=0 k=0
k k
f ( z 0 +∆ z ) −f ( z 0 ) ( z 0 + ∆ z ) −z 0 ∆z
k−1
k
f ( z )=z → lim
∆z→0 ∆z
= lim
∆ z→0 ∆z
= lim ∑
∆ z →0 ∆ z i=0
i
( z 0+ ∆ z ) z k−1−i
0
f ( z 0 +∆ z ) −f ( z 0 ) k−1
→ lim
∆z→0 ∆z
= lim ∑ ( z 0 +∆ z )i z k−1−i
∆ z → 0 i=0
0
k−1
=k z 0
k k k
z =r cos ( kθ ) +i . r sin ( kθ )
k
z =u ( x , y )+i . v ( x , y )
r =√ x 2 + y 2
θ=arctan ( yx )
∂ U ∂V
=
∂x ∂y
∂ V −∂U
=
∂x ∂y
( ( xy ))
k
u=( √ x + y )
2 2
cos k . arctan
1
arctan ( t )= 2
1+t
( ( )) y y
( ( ))
k−2 k−2
u x =kx ( √ x + y ) + k y ( √ x + y ) sin k .arctan
' 2 2 2 2
cos k . arctan
x x
'
u y =…
( ( xy ))
k
v=( √ x + y )
2 2
sin k . arctan
( ( )) y
( ( ))
y
k−2 k−2
v y =ky ( √ x + y ) + k x ( √ x + y ) cos k . arctan
' 2 2 2 2
sin k . arctan
x x
'
v x =…